Analisa Yuridis Implementasi Pengadaan Tanah Untuk Pembangunan Infrastruktur Pekerjaan Umum - Elza Syarief; Triana Dewi Seroja; Mukhtirili Mukhtirili (Journal of Law and Policy Transformation, 2020)
This thesis discusses the Implementation of Land Procurement for Development in the Public Interest in the Construction of the Kawal Reservoir Infrastructure, which was built by the Ministry of Public Works of the Director General of Water Resources. The background used is the issuance of regulations regarding land acquisition in the form of Law No. 2. In 2012, which is quite comprehensive regulates and facilitates the process of land acquisition for development in the public interest. This law has been revised 4 times in the form of a Perpres from the Presidential Regulation No. 71 of 2012 to the latest Presidential Regulation No. 88 of 2017 as a refinement and consistency of the government in the policy of accelerating infrastructure development. But the fact is that national land acquisition is still the second biggest inhibiting factor, 30%. Kawal Reservoir is an infrastructure development in the field of public works has become a polemic, starting from the systems and procedures for land acquisition, the policies issued by the parties, the substance of the problem, as well as the apparatus' view of the land acquisition itself. The implementation of land acquisition for development in the public interest is in accordance with Law No. 2 of 2012 on the construction of the guarding reservoir infrastructure, which at present is still continuing to stop its physical development at the preparation stage. Problems in the form of forest status functions, overlapping ownership, and the existence of the Governor of Riau Islands Province Decree regarding Location Determination are obstacles that are passed through the Spatial Planning and Land Affairs apparatus in carrying out their main duties and functions. The phenomena that exist in the background of the problem will be integrated with the literature, conceptual and frame of mind developed. Research using Empirical / Sociological Legal Research methods.